Pengaruh Gaya Belajar terhadap Kemampuan Pemecahan Masalah Matematika Siswa - Anjela Safira; Choirunnisah Choirunnisah; Iga Ayu Octavyanti; Nilam Dwi Apriliyani; Nimas Ayu Wigati (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
This research aims to determine the influence of learning styles on students' mathematical problem solving abilities. This research was carried out at MAS Al-Falah Klender. The method used is an ex post facto survey method with random sampling technique. The population in this study were class Data were collected using tests and analyzed by one way ANOVA. The results of this research show that 1) students' learning styles influence their mathematical problem solving abilities. 2) there is no significant difference between students' mathematical problem solving abilities with visual and auditory learning styles. 3) there is a significant difference between the mathematical problem solving abilities of students with kinesthetic and visual learning styles. 4) there is a significant difference between the mathematical problem solving abilities of students with kinesthetic and auditory learning styles.